Geospatial data bout the wildfire ignition probability and wildfire spreading capacity of Romanian vegetated surfaces - Artan Hysa (PANGAEA, 2021)
This data consist of a geospatial points layer (shp file), which deliver both the multi-criteria inventory records and the calculated wildfire ignition probability and wildfire spreading capacity (WIPI/WSCI) of the Romanian vegetated surfaces. The distance between points is 1km. The file consists of 70410 points in total, that overlap with the vegetated surfaces as derived from CORINE Land Cover data of 2018.